2023
DOI: 10.1161/hypertensionaha.122.19482
|View full text |Cite
|
Sign up to set email alerts
|

Increased Placental sFLT1 (Soluble fms-Like Tyrosine Kinase Receptor-1) Drives the Antiangiogenic Profile of Maternal Serum Preceding Preeclampsia but Not Fetal Growth Restriction

Abstract: BACKGROUND: Preeclampsia and fetal growth restriction (FGR) are both associated with an increased ratio of sFLT1 (soluble fms-like tyrosine kinase-1) to PlGF (placenta growth factor) in maternal serum. In preeclampsia, it is assumed that increased placental release of sFLT1 results in PlGF being bound and inactivated. However, direct evidence for this model is incomplete, and it is unclear whether the same applies in FGR. METHODS: We conducted a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Maternal biochemical markers fundamentally reflect placental function 30 . In recent years, PlGF, sFlt-1 and the sFlt-1/PlGF ratio have become popular markers for evaluating placental insufficiency 31 . We found that lower levels of PlGF were associated with a higher risk of FGR, which is consistent with previous research 15,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Maternal biochemical markers fundamentally reflect placental function 30 . In recent years, PlGF, sFlt-1 and the sFlt-1/PlGF ratio have become popular markers for evaluating placental insufficiency 31 . We found that lower levels of PlGF were associated with a higher risk of FGR, which is consistent with previous research 15,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, Gaccioli et al [ 75 ] showed that although the sFlt-1/PlGF ratio was increased in both pre-eclampsia and FGR in both placenta and maternal serum, in pre-eclampsia the sFlt-1/PlGF ratio was strongly associated with placental sFlt-1 concentrations ( r =0.45; P <0.0001) but not placental PlGF concentrations ( r =−0.17; P =0.16). In FGR pregnancies, however, the sFlt-1/PlGF ratio was strongly associated with placental PlGF concentrations ( r =−0.35; P =0.02) but not placental sFlt-1 concentrations ( r =0.04; P =0.81) suggesting that in pre-eclampsia the elevated sFlt-1/PlGF ratio is primarily driven by increased placental sFlt-1, whereas in FGR, it is mainly due to decreased placental PlGF.…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…In a more recent paper, Gaccioli [ 48 ] found that the triggers responsible for increasing the sFlt-1/PlGF ratio are different in pre-eclampsia than fetal growth restriction: in pre-eclampsia, sFlt-1 displays increased concentrations in the placenta, leading to the elevated sFlt-1/PlGF ratio, whereas in fetal growth restriction, reduced placental expression of PlGF causes the elevated sFlt-1/PlGF ratio. Moreover, among patients already diagnosed with early fetal growth restriction (<32 weeks), Palma Dos Reis [ 49 ] demonstrated that sFlt-1/PLGF values > 85 measured when the diagnosis was established were associated with a shorter time until delivery (1.9 ± 1.52 weeks vs. 5.7 ± 3.2 weeks for sFlt-1/PlGF ≤ 85), as well as higher prevalence of fetal demise, albeit independently of pre-eclampsia.…”
Section: Relevant Data From the Recent Literature Regarding The Value...mentioning
confidence: 99%